Variasi Pencampuran Daging Ikan Gabus dengan Tempe Kedelai pada Pembuatan Sosis Ditinjau dari Sifat Fisik, Organoleptik, dan Kadar Protein - Agtari N I; Noor Tifauzah; Elza Ismail (JURNAL NUTRISIA, 2017)
Background : Sausage is processed minced meat which is mixed with spices. Generally, sausage is made of beef which contains high cholesterol. It is not suitable to be consumed by anyone who has high blood pressure or who has high cholesterol in blood. Moreover, the price of beef in the market is quite expensive. Thus, alternatif option is needed to replace the main ingredient in order to be affordable for all people. Objective : The aim of this research is to determine the chracteristics of sausage product with mixed variation of common snakehead fish and soybean tempeh based on phisical characteristics, organoleptic characteristics, and protein content. Method : This research was a quasi-experimental with simple random design. Observation of physical characteristics was analizeddesciptively. Organoleptic charecteristic was analized by Kruskall-Wallis Test,it was continued to Mann Whitney Test if there was a difference. Protein content was analized desciptively. The results of physical characteristic were more soybean tempeh added, the color of sausage was more brown, the fishy smell was reduced, the taste of tempe was stronger, the taste of fish was reduced, and also the texture was softer. Result : The result of organoleptic charecteristics of the sausage which gets highest positive response on color and taste was sausage which has mixture of 80% common snakehead fish and 20% soybean tempeh. For smell and texture, sausage which gets highest positive response was sausage which has mixture of 90% common snakehead fish and 10% soybean tempeh. The result of protein content was more soybean tempeh added, the protein content was smaller. Conclusion : The conclucion of this research is mixing soybean tempeh influences the characteristics of sausage based on physical characteristics, organoleptic characteristics, protein content. Key words : sausage, common snakehead fish, soybean tempeh, physical characteristic, organoleptic characteristic, protein